ANALISIS KELAYAKAN EKONOMI PENGOPERASIAN SISTEM PENYEDIAAN AIR MINUM (SPAM) DI PULAU NUSA PENIDA - KABUPATEN KLUNGKUNG - Ariantana, Ketut; Sudiana Mahendra, Made; Nuarsa, I Wayan; Adnyana, I Wayan Sandi; Kastini Adiputri, Ni Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2023)
Water is the most basic need for living things, it follows population growth and development activities as in Nusa Penida Island. The water supply on this island comes from SPAM Penida and SPAM Guyangan. The Central and Provincial Governments of Bali provide operational subsidies of more than 7 billion on average. Perumda Panca Mahottama’s services also can’t cover all villages on this island. It means SPAM management is not yet economical, and the service is not optimal. The purpose of this economic feasibility analysis is to determine the economic feasibility of SPAM in terms of Full Cost Recovery and appropriate tariffs so that operational costs are proportional to income. To determine the economic feasibility conditions, a study was conducted to evaluate the value of current tariff (2021). The result is Opex value is bigger than the income value. This results in a NCF value of (-Rp.2,610,621,409.00). The operational cost is IDR.7,164,857,259.00/year with total production 1,530,362.88m3/year. The FCR value obtained was IDR.4,681.80/m 3 . The average production cost is IDR.2,975.92/m 3 , which means there will still be a loss in 2021 of IDR1,705.99/m 3 . Analysis was conducted based on the trial error method with calculation period of 15 years, with 3 different tariff systems, alternative 1, tariff with the same value IDR.4,100/m3 from 2023 to 2036, alternative 2 tariff is IDR.3,500 in 2023 to 2027 increase by IDR.1,000/m3 in 2028 to IDR.4,500/m3 until 2036. Alternative 3 tariff is IDR.3,000/m3 in 2023 increase by IDR.500/m3 in 2024 to 2026 and settled at a rate IDR.4,500/m3 until 2036. Keywords: SPAM; feasibility; economy; tariff